The distribution and regional determinants of nationally financed emissions-reduction projects in China. (May 2021) - Cong, Ren; Lo, Alex Y.; Yu, Wei
Abstract: As the Clean Development Mechanism (CDM) has experienced a decline in investments, major host countries in this mechanism have met with a surplus capacity in the production of carbon offset credits. One of these countries is China, which has turned its focus to its own emission trading institutions, such as the 'China Certified Emission Reduction' (CCER) scheme, a domestic carbon offsetting mechanism. In this study, we analyse this mechanism by identifying the regional determinants of the emissions-reduction projects. We examine the distribution of 2789 projects of China Certified Emission Reduction scheme and use regional economic attributes to predict the number of projects in 30 Chinese Provinces. Results from a panel data analysis indicate that these projects are more likely to be implemented in locations where per capita GDP is lower, CO2 emissions is higher, energy intensity is higher, and the amount of domestic loan is larger. This voluntary carbon market in China continues to demonstrate economic sensitivity in project implementation as it moves towards a new governing system in the post-CDM context. These findings could provide insights into the prospects for market-driven emission reduction initiatives in China and facilitate their mitigation actions. Highlights: China has created its own system for generating carbon emissions-reduction credits. We extracted data from a total of 2789 emissions-reduction projects in China. We identified the regional determinants of these projects using panel data analysis. More projects in less developed areas with greater access to domestic finance. The distribution of these projects is consistent with standard economic theory.